Future of clinical leadership: saving our greatest intensity for human beings. Issue 3 (8th August 2017) - Harrison, Marc
Abstract : Do the qualities that distinguish good doctors always lead to success in the operational space? The few studies that have explored this question suggest they can, though it's not a guarantee, and there may be a tension. This article looks at the studies and suggests that with the global healthcare landscape changing so rapidly—politically, economically and technologically—introducing physicians to the craft of leadership in the operational space may be more important than ever. It can also be more rewarding than ever, so long as clinicians don't lose sight of what it is they can uniquely offer as physician leaders. The article concludes that clinicians may be uniquely positioned to connect important points being raised about the healthcare ecosystem back to the reason it exists in the first place: to support caregivers in the sacred act of healing the sick, of preserving human life and human potential. 'Saving our greatest intensity for human beings' is ultimately what must distinguish clinical leaders.